A psychobiography of John F. Kennedy, Jr. : understanding his inner life, achievements, struggles, and courage - Ponterotto, Joseph G. (Charles C. Thomas, Publisher, 2018)
This book represents a psychobiographical story of John F. Kennedy, Jr. It covers JFK Jr.'s search for identity and purpose, and the depths and vibrancy of his personality. The author approaches the life of JFK, Jr. as a psychologist and psychobiographer with the goal of understanding the workings of John's mind; his inner feelings, fears, hopes, and desires perhaps not visible on the surface. This book will be an insightful resource to address unanswered questions about JFK Jr.'s life and potential future had he lived a full life.